2016
DOI: 10.1093/jnci/djv436
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of Benefits and Harms in US Cancer Screening and Prevention Guidelines: Systematic Review

Abstract: Sixty-nine percent of cancer prevention and screening recommendation statements either did not quantify benefits and harms or presented them in an asymmetric manner. Improved presentation of benefits and harms in guidelines would better ensure that clinicians and patients have access to the information required for making informed decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 31 publications
2
41
0
1
Order By: Relevance
“…The inclusion of harms associated with screening is another innovative characteristic of the new guidelines, especially in the Brazilian context, where this kind of outcome is rarely addressed in clinical guidelines. A recent systematic review found that 69% of guidelines that were identified for cancer prevention or early detection either failed to quantify the harms and benefits or presented them asymmetrically 21 . Thus, although the inclusion of harm outcomes is recommended by GRADE (Grading of Recommendations, Assessment, Development, and Evaluation), its implementation in guidelines for early detection of cancer is still incipient, even in the international context.…”
Section: Evolution Of Evidence On Early Detection Of Breast Cancer Anmentioning
confidence: 99%
“…The inclusion of harms associated with screening is another innovative characteristic of the new guidelines, especially in the Brazilian context, where this kind of outcome is rarely addressed in clinical guidelines. A recent systematic review found that 69% of guidelines that were identified for cancer prevention or early detection either failed to quantify the harms and benefits or presented them asymmetrically 21 . Thus, although the inclusion of harm outcomes is recommended by GRADE (Grading of Recommendations, Assessment, Development, and Evaluation), its implementation in guidelines for early detection of cancer is still incipient, even in the international context.…”
Section: Evolution Of Evidence On Early Detection Of Breast Cancer Anmentioning
confidence: 99%
“…The rationale of such a strategy lies on the limitations of PCa screening and diagnosis, which entails offering systematic transrectal ultrasound-guided biopsy (SB) to men presenting high levels of serum prostate-specific antigen (PSA) and/ or a suspicious digital rectal examination (DRE). First, many men without PCa manifest elevated PSA levels and undergo unnecessary biopsies, which often detect clinically insignificant cancers [4]. In addition, SB may miss up to 20% of cancers [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the positive predictive value of a raised PSA and subsequent TRUS guided biopsies is low [4], which leads to a considerable number of men undergoing unnecessary biopsies and a marked increase in the detection of clinically insignificant cancer [5]. This has significant cost implications and exposes patients to the inherent risk of biopsy and treatment [6].…”
Section: Introductionmentioning
confidence: 99%